STATE RESPONSIBILITY AND VICTIM’S REPARATIONS IN INDONESIA: THEORY OF LAW PERSPECTIVE - Andrey Sujatmoko (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2019)
Gross human rights violations are an internationally wrongful act which entails responsibility to the wrongdoer state to conduct reparations. Based on the principle of state responsibility, the said obligation appears because thr wrongdoer state has already breached an international obligation under international law. Indonesia still has the past gross human rights violations cases that were not settled yet, including the reparations issue of its victims. This article will analyse state responsibility theory, lawstate theory, and development law theory as the theory of law to explain legal obligation of state to conduct reparations toward the victims of the said violations.